Myorelaxant action of the Dysphania ambrosioides (L.) Mosyakin & Clemants essential oil and its major constituent α-terpinene in isolated rat trachea. (30th September 2020) - Pereira-de-Morais, Luís; Silva, Andressa de Alencar; da Silva, Renata Evaristo Rodrigues; Ferraz Navarro, Daniela Maria do Amaral; Melo Coutinho, Henrique Douglas; Menezes, Irwin Rose Alencar de; Kerntopf, Marta Regina; Cunha, Francisco Assis Bezerra da; Leal-Cardoso, José Henrique; Barbosa, Roseli
Highlights: The OEDa and its α-terpinene possess a myorelaxant effect in tracheal tissue. The α-terpinene potentiate the effect of acetylcholine. The EODa and the α-terpinene have potential as future therapeutic agents. Abstract: This study aimed to investigate the myorelaxant action of the Dysphania ambrosioides essential oil (EODa) and its major constituent α-terpinene on tracheal smooth muscle isolated from rats. In tracheal smooth muscle ex vivo, in organ baths, isometric contractions recordings were done in order to evaluated the effect of EODa (1–1000 μg/mL) and α-terpinene (1–3000 μg/mL) on the following parameters: basal tone, contractions evoked by potassium (KCl 60 mM), acetylcholine (ACh 10 μM) or serotonin (5-HT 10 μM). The EODa and its major constituent α-terpinene, did not statistically alter basal tone; however, they induced myorelaxant effects on top of contractions induced by KCl, ACh and 5-HT. EODa and α-terpinene also inhibited the contractions induced by barium in presence of High [K + ] (80 mM). The data suggest that the relaxation induced by these agents is caused by the inhibition of L-type VGCC, inhibiting the inward Ca 2+ current through these channels, but does not exclude the possibility of participation of other mechanisms. Results from this study also suggest the EODa, due to their efficacy on relaxation of the respiratory tract, posses a therapeutic potential as a antispasmodic agent for respiratory tract.